1994
DOI: 10.7863/jum.1994.13.8.595
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral artery Doppler ultrasonography for prediction of outcome after perinatal asphyxia.

Abstract: Perinatal asphyxia is the most common cause of neurologic injury and neurodevelopmental delay. The signs of injury are nonspecific at birth, and most indicators take hours to days before they become manifest. Early recognition of the injury is important in guiding management during those critical first days of life. Over a five‐year period, we investigated 16 term neonates with a history of asphyxia on the first day of life who demonstrated on intracranial Doppler sonography cerebral vessel high diastolic flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 9 publications
2
44
1
3
Order By: Relevance
“…12,20,21 Increased CBFV in the cerebral circulation by the age of 12 h in infants with severe HIE or poor outcome has been reported. 20,22 Increased CBFV from 24 to 72 h has been taken as a sign of permanent brain damage with poor prognosis in asphyxiated infants, [12][13][14] and the present results confirm the findings concerning increased CBFVs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…12,20,21 Increased CBFV in the cerebral circulation by the age of 12 h in infants with severe HIE or poor outcome has been reported. 20,22 Increased CBFV from 24 to 72 h has been taken as a sign of permanent brain damage with poor prognosis in asphyxiated infants, [12][13][14] and the present results confirm the findings concerning increased CBFVs.…”
Section: Discussionsupporting
confidence: 81%
“…CTG has a high sensitivity but low specificity for fetal hypoxia or asphyxia. 11 Increased cerebral blood flow velocity (CBFV) and resistive index reduced below 0.55 by pulsed Doppler ultrasonography, have been associated with poor outcome in birth asphyxia assessed at the age from 24 to 72 h. [12][13][14] We have previously shown a strong association of increased systolic CBFV in the anterior cerebral (ACA) or in the basilar (BA) arteries at around 24 h of age with adverse neurological outcome at the age of 1 year, whereas reduced resistive index failed to show association with poor outcome (submitted/unpublished data). In this study, we sought to analyse the obstetric parameters, biochemical asphyxia markers, HIE symptoms or their combinations, in predicting the neurological outcome at 1 year in full-term asphyxiated infants.…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos sobre a dopplerfl uxometria pela ultra-sonografi a transfontanela em recém-nascidos têm sido realizados, demonstrando um declínio fi siológico progressivo do IR com a idade cronológica 16 , e alterações dos valores de IR em condições patológicas, como por exemplo na hipóxia [17][18][19][20][21][22][23][24][25] . Porém este pare- Em estudos correlatos utilizando o Doppler transfontanela para a avaliação da EHI em RN a termo, não foram excluídos RN com alterações morfológi-cas detectadas pela USTF [17][18][19][20][21][22][23] .…”
Section: Discussionunclassified
“…Observaram diminuição dos valores de IR em RN com EHI grave ou moderada, associando os valores menores ou iguais a 0,55, no período de seis horas a cinco dias de vida, a um pior prognóstico como morte no período neonatal e disfunção neurológica grave a longo prazo. Outros estudos incluíram RN com outras enfermidades além da asfi xia intra-parto 24,25 . Dos 20 RN incluídos neste estudo, 15 apresentaram anormalidades transitórias na avaliação neurológica e no desenvolvimento, com normalização a partir do final do segundo trimestre de vida.…”
Section: Discussionunclassified
“…Correlation of US findings of cystic periventricular leukomalacia (PVL) with neuropathologic data was evaluated in two studies. 11,12 Each study found 100% correlation between US S.S. Institute of Medical Science and Research Centre findings and neuropathologic data. In our study, we found that one infant had dilated bilateral ventricles with grade IV intra ventricular haemorrhage, one infant had agenesis of corpus callosum which is haemodynamicaly stable and went uneventfully.…”
Section: Discussionmentioning
confidence: 99%